Confinement effect on lateral particle migration in deoxyribonucleic acid solution - Jung, Yoonyoung; Jin, Daekwon; Shim, Tae Soup; Lee, Sung Sik; Kim, Ju Min (Physics of Fluids, 2023)
Lateral migration and focusing of particles in viscoelastic fluids have recently been widely exploited in various microfluidic applications, such as particle counting and separation. However, there are still many unresolved problems regarding the underlying mechanisms that induce lateral migration in polymer solutions. In particular, as the sizes of particles and polymers (e.g., radius of gyration) become comparable, continuum mechanics (constitutive modeling)-based analyses are expected to fail, which has not yet been investigated. If lateral particle migration occurs only due to conventional bulk viscoelastic effects, the equilibrium particle positions are expected to remain constant when the aspect ratio ( r p c ) of the particle to channel dimensions is nearly fixed. In this study, we found that as the channel dimension of the cross section decreases, a transition occurs in which individual polymers ( λ -deoxyribonucleic acid) behave as deformable particles, and consequently, the equilibrium positions change. This study contributes to clarifying the lateral particle migration in polymer solutions and can be applied to various applications, such as deformability-selective particle separation.
Keywords: Acid solutions; Channel dimension; Confinement effects; Lateral migration; Micro fluidic applications; Particle counting; Particle migration; Particle separation; Vis-coelastic fluids; Visco-elastic fluid